FEMINIST STANDPOINT THEORY : an Analysis of Muslims Women Interaction in SHAFINA Ummida Jogokariyan - Kusuma, Dwi Kartika; Asror, Fuad Mafatichul (UIN Sunan Kudus, 2022)
This article aims to analyze how the interaction of Muslim women in SHAFINA Ummida. This study uses Standpoint Feminist Theory by Nancy CM Hartsock and Julia T. Wood In a descriptive qualitative research. This research concludes that The SHAFINA contributes to enhace knowledge for Muslim women at Jogokariyan village. Muslim womens learn about Islamic values life during adolescence and married life. Ummida Jogokariyan Mosque gives Muslim women wider participation and enhaces the role of Muslim women in the Jogokariyan environment..